Experimental salmonellosis caused by Salmonella enteritidis phage types in mice - Ozturk, G; Ozer, H; Kalender, H (Scientific Technical Research Council Turkey, 1998)
In this study, pathological findings were observed in experimental salmonellosis in mice. S. enteritidis PT 1, 4 and 7 strains isolated from chikens were used. Suspensions containing 10(9) and 10(8) of bacteria were inoculated orally to 36 mice. Anorexia, dullness, mild diarrhea, shudder, fever and death were observed in 9 mice. No clinical signs were seen in other mice. In macroscobic examinations, enlargement of liver and spleen, hyperemia and watery content were observed in intestines. In microscobic examinations, hyperemia, degeneration, necrosis and reticular cell hyperplasy in spleen. In addition, hyperemia, epithelial degeneration and necrosis were seen in the intestines. In bacteriological examinations, S. enteritidis was isolated from liver, spleen and intestines of mice that were died. Bacteria was isolated at the end of the study from above mentioned organs in mice that were inoculated with PT 4. But, this bacterial agent was isolated from only intestines in mice that were inoculated with PT 1 and PT 7.
Keywords: S-enteritidis; phagetypes; pathological findings; mouse; experimental infection